If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -1x = 5yz + 4 Reorder the terms: 2 + -1x = 4 + 5yz Solving 2 + -1x = 4 + 5yz Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 4 + -2 + 5yz Combine like terms: 2 + -2 = 0 0 + -1x = 4 + -2 + 5yz -1x = 4 + -2 + 5yz Combine like terms: 4 + -2 = 2 -1x = 2 + 5yz Divide each side by '-1'. x = -2 + -5yz Simplifying x = -2 + -5yz
| x^6-2x^4+4x^2-8=0 | | 1+.8c=7 | | 8x+x=12+104 | | 24+6y=-12 | | 20=2x+12 | | 51pt-3p+4t= | | y=2*1 | | 1x^2-9x-6=0 | | (x^2+6x+5)-(x^2+4x-5)= | | 2y+4=6y | | 4y-4=6y-22 | | (6x)-(x+8)= | | -6=6/5b+5 | | 8(y+5)+y=3(y+3)+2 | | 25-5x-18-12x=0 | | y=1+5 | | 9x-19=2x+11 | | 6x-x=60+30 | | x^2-6x+153=0 | | 16a*2-14a+1a*2-3a= | | 25-5x-18-12x=10 | | x^2-6+153=0 | | 15x+6-(X+2)= | | 0.25(m+5)=-1.5 | | 12x=10x+60 | | 10y=-22 | | 1+6h=2+4h | | 14x-5=10x+7 | | 7y-14=21 | | =k^2+4k+4 | | -7(x+5)=35 | | 5w-4=6 |